Review of the Afrotropical genus Dracontogena Diakonoff, 1970 (Lepidoptera, Tortricidae) with descriptions of eight new species - Aarvik, Leif; Karisch, Timm; Marthinsen, Gunnhild (Zootaxa, 2012)
The Afrotropical genus Dracontogena Diakonoff is reviewed, and the genitalia of the 15 species present in mainlandAfrica are illustrated. Eight new species are described: Dracontogena agassizi, D. rubondoensis, D. bjornstadi, D.angolensis, D. solii, D. kingstoni, D. gilligani and D. sundi. Dracontogena niphadonta continentalis Karisch is elevatedto species rank; Dracontogena hoppei Karisch is synonymised with D. continentalis Karisch; and Fulcrifera deltozyga(Meyrick) is transferred to Dracontogena, new combination. Twelve specimens were subjected to DNA barcoding, andsequence data from four additional specimens were used from the German LEPDE BOLD-project. A neighbour-joining tree is provided. A key to males of all known species is given.